Fatigue in Parkinson’s disease: Brazilian validation of the modified fatigue impact scale - LOPES, Josiane; ARAÚJO, Hayslenne Andressa Gonçalves de Oliveira; SMAILI, Suhaila Mahmoud (Arquivos de Neuro-Psiquiatria, 2020)
Background: The instruments that measure the impact of fatigue on physical, cognitive and psychosocial aspects has yet to be validated in Brazilian population with Parkinson’s disease (PD). The aim of this study was to cross-culturally adapt and assess the psychometric properties of the Brazilian version of the Modified Fatigue Impact Scale (MFIS-PD/BR). Methods: Ninety PD individuals were recruited. The adaptation of the MFIS-PD was performed by translation and back translation methodology. Psychometric analysis was applied in order to perform the administration of the socio-clinical questionnaire, Mini-Mental State Examination (MMSE), Unified Parkinson’s Disease Rating Scale (UPDRS Part I-IV), Hoehn-Yahr disability scale (HY), hospital anxiety and depression scale (HADS), Geriatric Depression Scale (GDS), fatigue severity scale (FSS), Parkinson Fatigue Scale (PFS-16), and MFIS-PD/BR with retest of the MFIS-PD/BR after 7 days. Results: The adaptation phase kept the same items of original MFIS-PD. The Cronbach’s alpha for the MFIS-PD/BR was 0.878 when all responses items were scored. The test-retest intraclass correlation coefficients was above 0.80 (p<0.01) for the MFIS-PD/BR score, which was moderately correlated with the HADS, GDS, MDS-UPDRS score total and non-motor experiences of daily living, FSS and PFS-16. It was revealed the MFIS-PD/BR>29 points as cut-off point to indicate fatigued subjects with accuracy of 0.835 (p<0.001). Conclusions: The MFIS-PD/BR is valid and reproducible to use in assessing the fatigue symptom in Brazilian PD subjects.
Keywords: Parkinson Disease; Fatigue; Validation Studies; Psychometrics